PEMBERDAYAAN PEMUDA TANI AKTIF SEBAGAI RELAWAN DESA MELAWAN COVID 19 - Herry Prasetyo; Sugeng Riyadi; Ulfah Agus Sukrillah (Universitas Jenderal Soedirman, 2021)
The Covid-19 pandemic has had an impact on social, economic and health lives in both rural and urban communities in Indonesia. The purpose of this community service activity is to empower active young farmers as village volunteers against Covid-19 in Klinting village, Banyumas Regency. The community service is to protect from the spread of covid-19, and increased public awareness in the prevention and control of covid-19. This community service activity has been carried out in the Klinting village, Banyumas Regency, involving five active young farmers to become volunteers to fight the spread of Covid-19, two village health volunteers and facilitated by village officials. The form of service activities that have been carried out is in the form of volunteers training on the prevention of Covid-19, health checks for vulnerable villagers, especially the elderly, monitoring people in monitoring at the village hall as a place of quarantine and educating residents about the prevention of Covid-19. The results that have been achieved in this activity were the village community collectively, mutual cooperation, work hand in hand, helping each other and keeping them healthy during the COVID-19 pandemic that is spreading. As a result, the community has the ability to break the chain of the spread of Covid-19 in their territory through new habits, namely washing hands with soap, wearing masks and maintaining a physical distance of 1-2 meters.